Advances in the Research of Aquatic Environment Volume 2 - Lambrakis, Nicolaos; Stournaras, George; Katsanou, Konstantina; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The book focuses on the management of the aquatic environment. It is aimed at scientists, students, governmental officials and specialists dealing with groundwater and environment. Its main goal is to inform the reader of ideas, knowledge and experience in terms of a sustainable aquatic environment. The main topics are as follows: Water Bodies and Ecosystems; Climate Change and Water Bodies; Water quality and agriculture; Interaction of Surface and ground waters; Karst Hydrogeology; Continuous Media Hydrogeology; Fissured Rocks Hydrogeology; Hydrochemistry; Geothermics and thermal waters; The role of water in construction projects; Hydrology
Fissured Rock Hydrogeology -- Hydrochemistry -- Water Quality and Agriculture -- Geothermics and Thermal Waters -- The Role of Water in Constructions Projects.
Keywords: Geography; Hydraulic engineering; Climatic changes; Environmental pollution; Earth Sciences; Hydrogeology; Climate Change; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution